2022
DOI: 10.3390/diagnostics12112829
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Linked Aptamer Assay for SARS-CoV-2 Spike-Protein: A Step-by-Step Performance Analysis in Clinical Samples

Abstract: The COVID-19 pandemic has been a main concern over the last two years and has become one of the most important crises in the history of human health. Today, there is still a need for affordable and reliable diagnostic tests for massive disease monitoring. Previously, a set of highly specific DNA-aptamers (C7/C9) binding to the SARS-CoV-2 Spike (S) protein were isolated but its performance in clinical samples remained to be tested. Here, 242 samples were collected through three different methods and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The LOD of N protein in this digital method was 33.28 pg/mL, showing a 300 times lower detection limit than the traditional ELISA method [ 78 ]. Fluorescence-linked aptamer assays (FLAA) have been reported as a sandwich-type detection system using fluorescence modification directly on an aptamer without enzymatic linkage [ 77 , 104 ]. As the fluorescence sensor utilized inorganic material, gold nanostar (AuNS), which changed the shape of AuNPs, detected specific SARS-CoV-2 S protein or SARS-CoV-2 pseudo-typed baculovirus in 10 min through distance-dependent nanoparticle surface energy transfer (NSET) spectroscopy (an LOD of 130 fg/mL for antigen and 8 particles/mL for virus) [ 82 ].…”
Section: Aptamersmentioning
confidence: 99%
“…The LOD of N protein in this digital method was 33.28 pg/mL, showing a 300 times lower detection limit than the traditional ELISA method [ 78 ]. Fluorescence-linked aptamer assays (FLAA) have been reported as a sandwich-type detection system using fluorescence modification directly on an aptamer without enzymatic linkage [ 77 , 104 ]. As the fluorescence sensor utilized inorganic material, gold nanostar (AuNS), which changed the shape of AuNPs, detected specific SARS-CoV-2 S protein or SARS-CoV-2 pseudo-typed baculovirus in 10 min through distance-dependent nanoparticle surface energy transfer (NSET) spectroscopy (an LOD of 130 fg/mL for antigen and 8 particles/mL for virus) [ 82 ].…”
Section: Aptamersmentioning
confidence: 99%
“…This sandwich-type detection strategy exhibits high sensitivity and specificity and is suitable for applying the lateral flow strip type kit for on-site diagnosis [37]. Franco-Urquijo et al reported an aptasensor that can diagnose SARS-CoV-2 through the FLAA test [38]. They designed a sandwich-type detection system using C7/C9 aptamers that can specifically bind to the SARS-CoV-2 spike (S) protein.…”
Section: Fluorophore-linked Aptamer Assay (Flaa)mentioning
confidence: 99%
“…(1) they can be easily modified into an aptamer, (2) they are inexpensive, and (3) a variety of natural and synthetic fluorophores are well known and can be selected depending on the purpose [58][59][60]. Previously developed organic dyes, fluorescein and rhodamine, are still used as fluorophores in aptasensors [30,32,35,38,54,57]. However, these previous fluorescent organic dyes have problems such as hydrophobicity, photobleaching, and being affected by pH changes [61].…”
Section: Organic Molecules As Fluorescent Probesmentioning
confidence: 99%
“…1 ). While previous studies have successfully developed SARS-CoV-2 antibody-based analysis methods for N protein detection and aptamer-based analysis methods for spike protein (S) detection in nasopharyngeal samples or antibody detection in serum samples [ 14 , 15 ], none of these methods have demonstrated sufficient sensitivity for effective prevention and control. This research introduces a more convenient and cost-effective aptamer-antibody hybrid method for aiding in the prevention and control of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%